2018
DOI: 10.1144/jgs2017-121
|View full text |Cite
|
Sign up to set email alerts
|

Geochronological and geochemical constraints on the coexistent N-MORB- and SSZ-type ophiolites in Babu area (SW China) and tectonic implications

Abstract: Supplemental file 1 Geology of the Babu ultramafic-mafic complex and sample DescriptionsThe Babu ultramafic-mafic complex in the Malipo county, southeastern Yunnan, outcrops in a tectonic nappe between the NW-striking Wenshan-Malipo and Funing strike-slip faults (Fig. 2a; YunnanBGMR 1990). The autochthonous strata are Devonian and Triassic argillaceous and sandy turbidites. The exotic Permian-Carboniferous limestones overlying structurally onto the turbidites may have been deposited originally in seamounts or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 101 publications
1
6
0
Order By: Relevance
“…Some authors have suggested the existence of an oceanic crust between north Vietnam and South China, of which remnants are preserved along the so-called Dian Qiong suture. Along this zone, Early Carboniferous-Permian gabbro, pillow basalts, and mafic dykes have been found in in NE Vietnam, Yunnan, and Guangxi Provinces, and were interpreted as the "Babu ophiolites" (Cai and Zhang, 2009;Halpin et al, 2016;Liu et al, 2018;Tran et al, 2007).…”
Section: Early Carboniferous (Visean)-middle Permian Evolutionmentioning
confidence: 99%
“…Some authors have suggested the existence of an oceanic crust between north Vietnam and South China, of which remnants are preserved along the so-called Dian Qiong suture. Along this zone, Early Carboniferous-Permian gabbro, pillow basalts, and mafic dykes have been found in in NE Vietnam, Yunnan, and Guangxi Provinces, and were interpreted as the "Babu ophiolites" (Cai and Zhang, 2009;Halpin et al, 2016;Liu et al, 2018;Tran et al, 2007).…”
Section: Early Carboniferous (Visean)-middle Permian Evolutionmentioning
confidence: 99%
“…Given the detrital zircon age spectra of five sandstone samples (Figure 4a-e), the G1 is similar to the ages of island volcanic arc (c. 256-240 Ma) in Napo, Jingxi and Pingxiang areas (Gan et al, 2021;Hu et al, 2012;Liu, Li, et al, 2018;Qin et al, 2011Qin et al, , 2012Xiang et al, 2021) and scattered granitic plutons in the NVT (Chen et al, 2014;Roger et al, 2012). The G2 are consistent with the tim- et al, 1993) and diagenetic K-metasomatism (Fedo et al, 1995), respectively; (b) Ternary Al 2 O 3 -Zr-TiO 2 plot (after Garcia et al, 1994) the Early Carboniferous-Middle Permian (Liu, Peng, & Guo, 2018;Tran et al, 2007;Zhang et al, 2013), younger than the age of Jinshajiang-Ailaoshan-Song Ma-Song Chay ocean (439-280 Ma, Jian et al, 2009a, 2009bVuong et al, 2013). After the intense and short tectonothermal activity induced by the Emeishan plume (c. 260 Ma, Fan et al, 2008;Zhou et al, 2006), this ocean started and continued to subduct Roger et al, 2012), which led to the widespread syncollision felsic magmatism and strong tectonic deformation (Faure et al, 2014(Faure et al, , 2016Lepvrier et al, 2011).…”
Section: Provenance and Tectonic Settingmentioning
confidence: 66%
“…The western DQS extends NW‐SE to the south of the Nanpanjiang foreland basin, South China and was interpreted as the potential suture zone between the SCB and NVT (Figure 1a, Cai & Zhang, 2009). Given the existing geological evidence, the scattered ophiolites within this suture probably represent the dismembered crust of the Paleo‐Tethys branch ocean that opened and spread during the Early Carboniferous–Middle Permian (Liu, Peng, & Guo, 2018; Tran et al, 2007; Zhang et al, 2013), instead of a rift basin originated from the Emeishan mantle plume (Faure et al, 2014, 2016; Hoa et al, 2008, 2016). The Late Permian–Middle Triassic basalts, andesites and rhyolites in Napo, Jingxi and Pingxiang areas, to the north/northeast of the western DQS, are interpreted as island volcanic arc responding to the subduction of this ocean (Hu et al, 2012; Qin et al, 2011, 2012; Xiang et al, 2021).…”
Section: Geological Setting and Samplesmentioning
confidence: 98%
See 2 more Smart Citations